Analysis of the scientific output of university technical architecture teachers in Spain, 1980-2015. Journal survey indexed in WOS-SCOPUSCSIC( ICYT-ISOC) - Durán Álvarez, Joaquín Manuel (Revista General de Información y Documentación, 2016)
The research by technical architects teaching at Spanish universities in the last 35 years has been studied based on the scientific output itself. With the change in the title of the new degree, the increase in doctors and academic promotion has changed this knowledge area. On the basis of indexed documents and the journals in which they were published, determinations were made regarding the research completed, its listing in recognized data bases, and the publication habits of the journals involved. Furthermore, the number of publications by this group was compared by universities and journals. The study undertaken evidences a substantial change in the scientific output of technical architects in Spain.